Prisoner [compact disc] - Adams, Ryan (Paxamericana Records, 2017)
Since the release of his last original studio album in 2014, Ryan Adams released a cover of Taylor Swift's 1989 and toured around the world. Now he is back with a new release that includes the single Do You Still Love Me.